Attempts to Rifelmenise Vilnius in 1939–1940 - Nefas, Mindaugas (History / Istorija, 2020)
Annotation. Based on a rich database of sources (memories and documents stored in the Central State Archive of Lithuania), the article analyses the activities of the Lithuanian Riﬂemen’s Union in the Vilnius region regained in October 1939. Te main attention is paid to the XXIII Vilnius Riﬂemen’s Territorial Unit operating in Vilnius County, which was tasked with riﬂemenising the Lithuanian capital and surrounding territories. Te study clarifes the periodisation of riﬂemen activity in Vilnius, analyses in detail the process of team formation in 1939–1940, examines the tasks set for riﬂemen and their implementation in the regained land.